Clostridioides difficile aggravates dextran sulfate solution (DSS)-induced colitis by shaping the gut microbiota and promoting neutrophil recruitment. (31st December 2023) - Dong, Danfeng; Su, Tongxuan; Chen, Wei; Wang, Daosheng; Xue, YiLun; Lu, Qiuya; Jiang, Cen; Ni, Qi; Mao, Enqiang; Peng, Yibing
ABSTRACT: Clostridioides difficile is a pathogen contributing to increased morbidity and mortality of patients with inflammatory bowel disease (IBD). To determine how C. difficile affects the severity of colitis, we constructed a dextran sulfate solution-induced colitis model challenged with C. difficile . Without antibiotic administration, C. difficile led to transient colonization in mice with colitis, but still significantly enhanced disease severity as assessed by weight loss, histopathological damages, and inflammatory cytokine concentrations. Because this effect is independent of toxin production as shown by infection with a non-toxigenic strain, we focused on changes in the gut microbiota. The microbiota altered by C.difficile, featured with reduced proportions of g_Prevotellaceae_UCG-001 and g_Muribaculaceae, were confirmed to contribute to disease severity in colitis mice via fecal microbiota transplantations. The inflamed colon showed neutrophil accumulation by flow cytometric analysis and myeloperoxidase immunochemical staining. There was enrichment of upregulated genes in leukocyte chemotaxis or migration as shown by RNA sequencing analysis. The isolated neutrophils from C. difficile -infected mice with colitis showed a robust migratory ability and had enhanced expression of cytokines and chemokines. We observed a detrimental role of neutrophils in the progress of disease by hindering neutrophil recruitment with the CXCR2 inhibitor SB225002. Furthermore, neutrophil recruitment appeared to be regulated by interleukin (IL)-1β, as inhibition of IL-1β production by MCC950 markedly ameliorated inflammation with decreased neutrophil accumulation and neutrophil-derived chemokine expression. In conclusion, our study provides information on the complicated interaction between microbiota and immune responses in C. difficile -induced inflammation in mice with colitis. Our findings could help determine potential therapeutic targets for patients with IBD concurrent with C. difficile infection.